Management Practices, Workforce Selection, and Productivity - Bender, Stefan; Bloom, Nicholas; Card, David; Van Reenen, John; Wolter, Stefanie (Journal of Labor Economics, 2018)
We study the relationship among productivity, management practices, and employee ability using German data combining management practices surveys with employees’ longitudinal earnings records. Including human capital reduces the association between productivity and management practices by 30%–50%. Only a small fraction is accounted for by the higher human capital of the average employee at better-managed firms. A larger share is attributable to the human capital of the highest-paid workers, that is, the managers. A similar share is mediated through the pay premiums offered by better-managed firms. We find that better-managed firms recruit and retain workers with higher average human capital.